A Crohn’s Disease Patient Found to Have Entamoeba histolytica Infection Causing Pyogenic Liver Abscess - Hannah Saven; Ashton Harmacinski; Andrew Canakis; Uni Wong (Case Reports in Gastrointestinal Medicine)
Entamoeba histolytica is a parasite that typically causes amoebic dysentery but can result in complications such as pyogenic liver abscess. Patients with inflammatory bowel disease often take immunosuppressive therapies that make them more susceptible to such infections. Notably, parasitic infections in this context are rare in nonendemic areas. We describe a 57-year-old man who recently started infliximab therapy for Crohn’s disease and presented with fever and right upper quadrant pain. While hospitalized, this patient was diagnosed with Entamoeba histolytica liver abscess. This case demonstrates that parasitic infections should be considered early in immunocompromised patients with inflammatory bowel disease.